Nano-enabled weed management in agriculture: From strategic design to enhanced herbicidal activity - Forini, Mariana M.L. [UNESP] (2022)
The use of nanotechnology has emerged in the agricultural sector. In recent years, several nano-enabled materials have been reported for weed control. Nano-enabled herbicides (also called nanoherbicides) can be designed from organic, inorganic, or hybrid materials. These materials have unique properties such as small size, specific surface area, and the ability to control the release of metal ions and organic molecules in the agricultural field. Some studies have reported the ability of nanoherbicides to provide better weed management compared to non-nanoformulations. However, studies regarding the environmental risk assessment and mechanisms of action of nanoherbicides in plants are still incipient. Nevertheless, they are essential to ensure a safe application for human health and the environment. In this review, we outlined the current understanding of nano-enabled herbicides as well as some strategic design to fabricate nanostructures for weed control. Also, a critical discussion regarding the fate, behavior and effects of nanoherbicides in plants was addressed in order to achieve products for environmentally friendly and sustainable agriculture.